Diaminopimelic Acid Metabolism by Pseudomonadota in the Ocean - Li-Yuan Zheng; Ning-Hua Liu; Shuai Zhong; Yang Yu; Xi-Ying Zhang; Qi-Long Qin; Xiao-Yan Song; Yu-Zhong Zhang; Huihui Fu; Min Wang; Andrew McMinn; Xiu-Lan Chen; et al. (Microbiology Spectrum, 2022)
ABSTRACT Diaminopimelic acid (DAP) is a unique component of the cell wall of Gram-negative bacteria. It is also an important component of organic matter and is widely utilized by microbes in the world’s oceans. However, neither DAP concentrations nor marine DAP-utilizing microbes have been investigated. Here, DAP concentrations in seawater were measured and the diversity of marine DAP-utilizing bacteria and the mechanisms for their DAP metabolism were investigated. Free DAP concentrations in seawater, from surface to a 5,000 m depth, were found to be between 0.61 μM and 0.96 μM in the western Pacific Ocean. DAP-utilizing bacteria from 20 families in 4 phyla were recovered from the western Pacific seawater and 14 strains were further isolated, in which Pseudomonadota bacteria were dominant. Based on genomic and transcriptomic analyses combined with gene deletion and in vitro activity detection, DAP decarboxylase (LysA), which catalyzes the decarboxylation of DAP to form lysine, was found to be a key and specific enzyme involved in DAP metabolism in the isolated Pseudomonadota strains. Interrogation of the Tara Oceans database found that most LysA-like sequences (92%) are from Pseudomonadota, which are widely distributed in multiple habitats. This study provides an insight into DAP metabolism by marine bacteria in the ocean and contributes to our understanding of the mineralization and recycling of DAP by marine bacteria. IMPORTANCE DAP is a unique component of peptidoglycan in Gram-negative bacterial cell walls. Due to the large number of marine Gram-negative bacteria, DAP is an important component of marine organic matter. However, it remains unclear how DAP is metabolized by marine microbes. This study investigated marine DAP-utilizing bacteria by cultivation and bioinformational analysis and examined the mechanism of DAP metabolism used by marine bacteria. The results demonstrate that Pseudomonadota bacteria are likely to be an important DAP-utilizing group in the ocean and that DAP decarboxylase is a key enzyme involved in DAP metabolism. This study also sheds light on the mineralization and recycling of DAP driven by bacteria.